The Influence of Service and Brand Image on Garden Pet Shop Customer Purchasing Decisions Through Brand Trust - Muhammad Ibnu Rusydi; Ismail Razak; Eddy Sanusi P Silitonga (Madani Connection, 2024)
This study aims to: 1.) To describe service quality, brand image, brand trust and purchasing decisions of Garden Pet Shop customers. 2.) To analyze the effect of service quality and brand image on brand trust at Garden Pet Shop. 3.) To analyze the effect of service quality and brand image on Garden Pet Shop customer purchasing decisions. 4.) To analyze the effect of brand trust on Garden Pet Shop customer purchasing decisions. 5.) To analyze the effect of service quality and brand image on Garden Pet Shop customer purchasing decisions through brand trust. This research was conducted at Garden Pet Shop with a research sample of 100 respondents. The sampling technique used random sampling. The data analysis method uses descriptive analysis and quantitative analysis with path analysis. The results showed that: 1.) Service quality and brand image support increased brand trust. 2.) Service quality and brand image support increased purchasing decisions. 3.) Brand trust supports increased purchasing decisions. 4.) Service quality and brand image support service decisions through brand trust